AN ENZYME IN MAST CELLS WITH PROPERTIES LIKE CHYMOTRYPSIN - Benditt, Earl P. (The Rockefeller University Press, 1959)
Mast cells contain an enzyme which hydrolyzes 3-chloroacetoxy-2-naphthoic acid anilide. By using highly purified mast cells isolated by differential centrifugation in high density sucrose solutions we have been able to study this enzymatic activity in more detail. The enzyme has properties similar to those of chymotrypsin: Chymotrypsin will hydrolyze the histochemical substrate, and the chymotrypsin and mast cell activities with this substrate are similarly inhibited by diisopropylfluorophosphate. The mast cell enzyme is capable of hydrolyzing the N-acetyl esters of tryptophan, tyrosine, and phenylalanine, the relative rates of hydrolysis being similar to those seen with chymotrypsin. A characteristic trypsin substrate, p-toluenesulfonyl arginine methyl ester, is not acted upon by the mast cell enzyme or chymotrypsin. The pH activity curve of the new cell enzyme is similar to that of chymotrypsin as determined with N-acetyl-L-tryptophan ethyl ester as substrate.